The Mediated Relationship Between Received Support and Job Satisfaction: An Initial Application of Socialization Resources Theory. Issue 1 (1st January 2017) - Cranmer, Gregory A.; Goldman, Zachary W.; Booth-Butterfield, Melanie
Abstract : The relationship between support received within workplace friendships and employee job satisfaction is complicated. Extending Socialization Resources Theory (SRT), this study hypothesized that the relationship between received support (i.e., emotional, informational, and instrumental) and job satisfaction is mediated by employee organizational assimilation (i.e., familiarity with coworkers, acculturation, recognition, and involvement). The findings help explain the complex relationship between received support and job satisfaction, and demonstrate that assimilation is an influential third variable influencing employee experiences and attitudes.